Buckling of cylindrical shells under axial compression with loading imperfections: An experimental and numerical campaign on low knockdown factors. (June 2020) - Wagner, H.N.R.; Hühne, C.; Janssen, M.
Abstract: Thin-walled cylindrical shells are primary structures in aerospace, marine and civil engineering. A major loading scenario for these imperfection sensitive shells is axial compression. For this load case, there is a critical disagreement between the theoretical and experimental critical load. This difference is mainly contributed due to shape deviations of the shell middle plane which are commonly described as geometric imperfections. However, some deviations between theoretical and experimental buckling loads are sometimes so severe that other imperfection types are possibly to blame. This article describes experimental and numerical studies on the influence of loading imperfections on the buckling load of thin-walled cylinders. A global loading imperfection was applied by mistake during a buckling test of a thin-walled cylinder which led to a severe buckling load reduction and the corresponding load level was similar to the post-buckling load. Also, a series of experimental studies with localized loading imperfections is described which significantly reduced the buckling load of CFRP cylinders. The experimental results of this article represent an example for some of the very low buckling knockdown factors from early experimental campaigns and give insights in how to avoid these critical imperfections in experimental buckling campaigns. Highlights: Experimental buckling studies on cylinder under axial compression with different loading imperfections. Global loading imperfection leads to an extreme reduction of the buckling load. Local loading imperfections lead to a lower-bound of the buckling load. Numerical and experimental test structures are described in detail.